The Implementation of Zakat in the Economic Empowerment of the Muslim Community through BAZNAS - Miko Ananda Daulay; Ilham Mirzaya Putra (Suluah Pasaman, 2026)
This study aims to analyze how zakat is implemented as an instrument for the economic empowerment of Muslims through the BAZNAS of North Sumatra Province. It also explores the extent to which productive zakat contributes to improving the standard of living of beneficiaries, and maps the obstacles faced by beneficiaries when developing their productive businesses. This research is motivated by the persistently high level of poverty, which requires sustainable economic empowerment efforts. From an Islamic economic perspective, zakat plays a strategic role as an instrument for distribution and economic empowerment when managed productively. The study used a qualitative method with a descriptive approach. Data were obtained through observation, interviews, and documentation at BAZNAS of North Sumatra Province. The research findings show that the distribution of productive zakat by BAZNAS North Sumatra has a positive impact on the welfare of beneficiaries, particularly through assistance with business capital, mentoring, and business equipment support. This assistance has been proven to encourage business development, increase income, and help meet the educational and economic needs of beneficiary households. However, several obstacles remain, including limited marketing reach, intense business competition, and rising production costs that have the potential to disrupt the continuity of beneficiary businesses. Therefore, strengthening mentoring, expanding market access, and developing business networks are necessary to increase the effectiveness of productive zakat programs in a sustainable manner.